Adnexal masses: a true challenge - Pereira,Joana Lopes (2018)
Preoperative diagnosis of adnexal masses is still one of the greatest challenges for gynaecologists. Even though the majority of adnexal neoformations are benign, a careful evaluation to exclude malignancy is mandatory. The rapid evolution in the field of ultrasonography increased diagnostic accuracy and magnetic resonance imaging provides a valid contribution, but still, sometimes, the distinction between malignant and benign is difficult. We report a case of a premenopausal women who presented with a large and painful abdominal mass four months after an emergent caesarean delivery.